Synergistic Action of IL-8 and Bone Marrow Concentrate on Cartilage Regeneration Through Upregulation of Chondrogenic Transcription Factors - Yoon, Dong Suk; Lee, Kyoung-Mi; Kim, Sung-Hwan; Kim, Su Hee; Jung, Youngmee; Kim, Soo Hyun; Park, Kwang Hwan; Choi, Yoorim; Ryu, Hyun Aae; Choi, Woo Jin; Lee, Jin Woo (MARY ANN LIEBERT, INC, 2016)
The objective of this study was to determine whether a biphasic scaffold loaded with a combination of a chemokine and bone marrow concentrate (BMC) could improve tissue regeneration in knee articular cartilage of beagles with cylindrical osteochondral defects. For this investigation, an osteochondral defect (6mm in diameter and 8mm deep) was created in the weight-bearing articular surface of the femoral medial condyle in beagles. Bone marrow was aspirated from the posterior iliac crests of beagles to obtain mesenchymal stem cells (MSCs) for in vitro assay. Hematoxylin and eosin (HE), Masson's trichrome (MT), safranin O/fast green staining, and immunohistochemistry were performed for histological analysis. Quantitative real-time polymerase chain reaction was performed to understand the roles of BMC in chondrogenic differentiation of MSCs. At 12 weeks after transplantation of biphasic scaffolds, we observed that interleukin-8 (IL-8) or the combination of IL-8 and BMC induced massive bone regeneration compared to saline, BMC only, and MSCs. In gross appearance, the osteochondral defect site was nearly completely filled with repair tissue in the group that received the combination of IL-8 and BMC but not in the other groups. Moreover, histological analysis showed obvious differences in cartilage regeneration among groups. HE and MT staining showed that the cartilage defect sites of the group receiving the combination of IL-8 and BMC were regenerated with cartilage-like tissues showing chondrocyte morphology. Safranin O staining showed hyaline cartilage regeneration in the group receiving IL-8 and BMC, whereas fibrous-like tissues were formed in the other groups. Furthermore, immunostaining revealed the presence of type II collagen and aggrecan in regenerated cartilage tissue of the group receiving IL-8 and BMC, whereas regenerated cartilage tissues of the other groups weakly expressed type II collagen and aggrecan. These results indicate that the combination of a chemokine IL-8 and BMC has significant positive effects on osteochondral regeneration in a beagle model through enhancing expression of the chondrogenic transcription factors and markers such as Sox9 and type II collagen.
Keywords: MESENCHYMAL STEM-CELLS; BETA-TRICALCIUM PHOSPHATE; ARTICULAR-CARTILAGE; GROWTH-FACTORS; ANIMAL-MODELS; CLINICAL-USE; FACTOR-I; DEFECTS; REPAIR; CHONDROCYTE